Recent advances and future frontiers in Pickering emulsions for food applications: Bridging science, industry, and nutrition - Kirtil, Emrah; Yildiz, Eda (Elsevier, 2025)
Pickering emulsions, in which solid colloidal particles assume the stabilizing role typically performed by surfactants, have witnessed rapid growth in food research and development. Their irreversible adsorption at the oil-water interface produces robust droplet armors that withstand temperature shifts, shear forces, and pH extremes, making them an appealing option across various product sectors. In food research, the past five years have brought notable progress in harnessing plant and biopolymer-based particles to address challenges of saturated fat reduction, extended shelf life, and controlled release of sensitive ingredients such as vitamins, antioxidants, and probiotics. These advances have yielded important findings in dairy applications-particularly for low-fat ice creams, yogurts, and nutrient-fortified milk analogs-as well as in baked goods, confectionery products, and emerging plant-based meat analogs requiring structured fat mimetics. Alongside fundamental insights into interfacial rheology and the kinetic stability of particle-laden droplets, investigations have explored regulatory perspectives, including GRAS/QPS status and allergen labeling, to facilitate larger-scale adoption. This review captures both the foundational science behind Pickering stabilization and the recent breakthroughs in product formulation, highlighting specific examples of enhanced texture, functional ingredient retention, and clean-label appeal. By assembling these diverse strands of research, it clarifies how Pickering emulsions have become a versatile, far-reaching strategy for safer, more sustainable, and increasingly functional food innovations.
Keywords: Pickering emulsions; Edible nanoparticles; Colloidal stability; Dairy applications; Clean-label formulations; Nutrient encapsulation; Lipid digestion kinetics; Regulatory frameworks